The impact of preterm birth on hospital inpatient admissions and costs during the first 5 years of life. - Petrou, S; Mehta, Z; Hockley, C; Cook-Mozaffari, P; Henderson, J; Goldacre, M (2003)
OBJECTIVES: To compare the cumulative use and cost of hospital inpatient services to 5 years of age by individuals divided into 4 subgroups by gestational age at birth. DESIGN: Costs applied to the hospital service utilization profile of each infant born in 2 areas covered by the Oxford Record Linkage Study during 1970-1993. SETTING: Oxfordshire and West Berkshire, southern United Kingdom. SUBJECTS: 239 694 individuals divided into 4 subgroups by gestational age at birth: <28 weeks, 28 to 31 weeks, 32 to 36 weeks, >or=37 weeks. MAIN OUTCOME MEASURES: Number and duration of hospital admissions during the first 5 years of life and costs, expressed in pound sterling and valued at 1998-1999 prices, of hospital inpatient services. RESULTS: The total duration of hospital admissions for infants born at <28 and at 28 to 31 gestational weeks was 85 and 16 times that for term infants, respectively, once duration of life had been taken into account. Hospital inpatient service costs were significantly higher for preterm infants than for term infants, with the cost differences persisting throughout infancy and early and mid-childhood. Over the first 5 years of life, the adjusted mean cost difference was estimated at pound 14,614 ( 22,798 US dollars) when infants born at <28 weeks gestational age were compared with term infants and pound 11,958 ( 18,654 US dollars) when infants born at 28 to 31 weeks gestational age were compared with term infants. Independent contributions to total cost came from being born: small for gestational age, a multiple, during the 1970s and early 1980s, to a woman of extreme maternal age or who was hospitalized antenatally, and from experiencing extended survival or childhood disease. However, preterm birth remained the strongest predictor of high cost. CONCLUSIONS: Preterm birth is a major predictor of how much an individual will cost hospital service providers during the first 5 years of life.